Efeito do selênio sobre a toxicidade do cloreto de mercúrio ('HG'CL IND. 2') em tilápia, Oreochromis niloticus (Linnaeus, 1757) - França, Jakeline Galvão de [UNESP] (2005)
This work had as objective to evaluate if the two forms of selenium (sodium selenite - Se4+ and sodium selenate - Se6+) have antagonistic effect to the toxic action of mercury chloride (HgCl2) through the acute toxicity (96h) and chronic (14 days), using the tilapia, Oreochromis niloticus. For the two types of tests the treatments had consisted of: I) control group; II) only Hg; III) only Se4+; IV) only Se6+; V) Se4+ + Hg and VI) Se6+ + Hg. For the test of acute toxicity, was used juveniles submitted to the concentration of 0.4 mg Hg . L-1 (considered mean lethal concentration - CL50) and in the concentration of 1.0 mg Se . L-1 (considered concentration of non observed effect of lethality - NOEL) for the sodium selenite (NaSe4+O3) and the sodium selenate (NaSe6+O3). The test period of chronic toxicity was 14 days with young tilapia in the following concentrations: 0.08 mg Hg . L-1, 0.4 mg Se4+. L-1 and 1.4 mg Se6+. L-1. The evaluation of the sub-lethal chronic effect had been carried through the hematological parameters: erytrocyte count (Er), hemoglobin level (Hb), hematocrit (Ht) and for the hematimetric indices (MCV, MCH and MCHC). In the test of acute toxicity significant difference (P>0.05) in the mortality indices between the mercury treatments and in the associations did not occurs (Hg + Se4+ and Hg + Se6+). In the hematological analyses significant difference (P<0.05) for MCHC of the concentration of association of mercury + selenate of sodium (Hg + Se6+) in the tenth day was verified. The results had demonstrated that the two used forms of selenium in the acute test were not efficient to minimize the mercury toxicity. In the test of chronic toxicity the treatment of association mercury + selenate of sodium provoked alterations in the blood of the tilápia